THE ANALYSIS LEADERSHIP STYLE OF STUDY PROGRAM LEADERS ON LECTURER PERFORMANCE STKIP BBG BANDA ACEH - Rahmattullah (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2018)
This study aims to examine the influence of leadership style of department to the performance of STKIP BBG Banda Aceh. The data were obtained by sampling to all lecturers at STKIP BBG Banda Aceh. From this research, it is found that leadership style of department leader has a significant influence on the performance of STKIP lecturers of BBG Banda Aceh. Any change in leadership style of the department leader in a positive direction will improve the performance of lecturer STKIP BBG Banda Aceh.